Pengembangan dan Pendampingan Hilirisasi Berbasis Model Hexahelix pada Olahan Dessert dan Krupuk Susu Sebagai Produk Unggulan Desa Samar, Kecamatan Pagerwojo, Kabupaten Tulungagung - Aan Fardani Ubaidillah; Ali Imron; Rochmawati Rochmawati; Dewi Ayu Sakdiyyah; Mufti Nawang Prastiko (Nusantara Mengabdi Kepada Negeri, 2024)
In the era of globalization, the empowerment of local potential has become increasingly important, especially at the village level. The village of Semar in Pagerwojo District, Tulungagung Regency, is a major dairy-producing area, with 60% of its population engaged in dairy farming. However, the Sri Wigati Dairy Cooperative (KUD), which has traditionally been the primary buyer of milk, is facing management issues, forcing farmers to sell their milk to private collectors with limited capacity. As a result, a significant portion of the milk goes unsold, posing a potential economic loss. To address this, a previous community service initiative taught farmers how to process milk into milk crackers, although these products have remained limited to local consumption despite their added value. Therefore, the focus must shift to the regional or national market. This community service program aims to: 1) enhance the competitiveness of local products, 2) empower the community, 3) optimize the value chain, 4) increase income, 5) develop a sustainable business model, 6) foster partnerships, and 7) improve community knowledge and skills. The outcomes of this initiative align with the established goals, marking a positive first step towards improving the welfare and economy of the Semar Village community.